A critical analysis of Section 21 of the Children's Act 38 of 2005 with specific reference to the parental responsibilities and rights of unmarried fathers - Boezaart, C.J. (Trynie) (University of Pretoria, 2014)
Dissertation (LLM)--University of Pretoria, 2013.